The Church of Ireland and the Royal Martyr: Regicide and Revolution in Anglican Political Thought c. 1660–c. 1745 - Connolly, S. J. (The journal of ecclesiastical history, 2003)
The survival in published form of a range of sermons commemorating the execution of Charles I provides an opportunity to examine the character and limits of political debate within the Church of Ireland. After 1688 the task of condemning the regicide of 1649 without seeming to question the legitimacy of the Revolution presented serious difficulties. In the longer term the anniversary ceased to be contentious, as defenders of the Hanoverian establishment appropriated much of the traditional Anglican rhetoric of obedience to lawful authority. That appropriation provides the context for a significant 30 January sermon by Jonathan Swift.